PENGARUH HARGA, FASILITAS DAN KUALITAS PELAYANAN TERHADAP MINAT BERKUNJUNG KE PEMANDIAN TIRTA RIA DI DESA SUMBEREJO KEC. NGASEM KAB. KEDIRI - Maulana, Vicy Cahya; Afandi, Tjetjep Yusuf; Surindra, Bayu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2025)
This research investigates the influence of price, facilities, and service quality on revisit intention to Tirta Ria Bathing Place in Sumberejo Village, Ngasem Subdistrict, Kediri Regency. A quantitative approach was employed, utilizing multiple linear regression analysis. Data were obtained through questionnaires completed by 259 respondents and analyzed using SPSS version 31. The results demonstrate that price, facilities, and service quality each exert a positive and significant influence on revisit intention, both individually (partially) and collectively (simultaneously). Among these variables, service quality stands out as the most dominant factor. The novelty of this study lies in its contextual relevance to the post-pandemic recovery of local tourism and in its comprehensive examination of the three variables in influencing revisit behavior. These findings provide practical insights for tourism managers in crafting effective strategies to boost visitor return rates and support sustainable tourism growth.